On Z. Bauman’s book ‘A Chronicle of Crisis: 2011-2016’, with the preface by Dr. N. Lawson. London, UK: Social Europe Edition 2017. 163 p. ISBN 978-1-9997151-0-6 - Yanitsky, Oleg N. (Advances in Social Sciences Research Journal, 2018)
Not Available